Effect of citric acid induced crosslinking on the structure and properties of potato starch/chitosan composite films. (December 2019) - Wu, Hejun; Lei, Yanlin; Lu, Junyu; Zhu, Rui; Xiao, Di; Jiao, Chun; Xia, Rui; Zhang, Zhiqing; Shen, Guanghui; Liu, Yuntao; Li, Shanshan; Li, Meiliang
Abstract: Potato starch/chitosan (PS/CS) films cross-linked with citric acid (CA) at different concentrations (5%–20%, w/w, on a dry basis of the weight of PS and CS) were developed via a solution blending-casting method, and their structure, water resistance, physical and mechanical properties, and antimicrobial activity were investigated. Fourier transform infrared spectra, X-ray diffraction and differential scanning calorimetry studies confirmed crosslinking among PS, CS and CA. Scanning electron microscopy images revealed that the cross-sectional fracture surfaces of all the films were smooth and homogenous, while the surface roughness of the CA cross-linked PS/CS films was higher than that of the uncross-linked films as also confirmed by the three-dimensional surface topography images. It was found that the properties of the films changed as the CA content varied, ascribing to the cosslinking and plasticizing effect of CA. The water resistance properties of the CA cross-linked PS/CS films were improved significantly when compared to the uncross-linked films. Moreover, the incorporation of CA could enhance the mechanical and antimicrobial properties of PS/CS films to some extent. Particularly, the results indicated that the films cross-linked with 15% CA showed the best comprehensive properties among all films. For example, the swelling degree of the films with 15% CA decreased from 686.4% to 98.1%, and water vapor permeability decreased from 3.03×10 −12  g cm/cm 2 ·s·Pa to 2.05 ×10 −12  g cm/cm 2 ·s·Pa, while the tensile strength was 29% higher than that of the uncross-linked film. However, excessive addition of CA in the composite films might solidify crystals on the film surface and have negative effects on their performance. This study provides a simple and effective pathway for preparation of polysaccharide-based films with improved properties, which have a potential as bioactive packaging material for food application. Graphical abstract: Image 1 Highlights: Potato starch (PS)/chitosan (CS) composite films cross-linked with citric acid (CA) were developed. CA acts both as a crosslinking agent and a plasticizer in the PS/CS films. The composite films had good compatibility and desirable water resistance after cross-linking. Addition of CA at appropriate level can obtain films with better mechanical and antimicrobial properties.